Anatomy of the upper respiratory tract in domestic birds, with emphasis on vocalization. (11th January 2018) - Casteleyn, C.; Cornillie, P.; Van Cruchten, S.; Van den Broeck, W.; Van Ginneken, C.; Simoens, P.
Summary: This work reviews the anatomy of the upper respiratory tract in domestic birds including the chicken and pigeon. Non‐exhaustive additional information on other bird species, illustrating the extraordinary diversity in the biological class Aves, can be found in several footnotes. The described anatomical structures are functionally considered in view of avian sound production. In particular, the Syrinx is invaluable. Its most important structures are the Labia and the lateral and medial tympaniform membranes in non‐songbirds and songbirds, respectively. These structures produce sound by vibrating during expiration and eventually inspiration.